2009
DOI: 10.1105/tpc.107.055988
|View full text |Cite
|
Sign up to set email alerts
|

The ER Chaperone LHS1 Is Involved in Asexual Development and Rice Infection by the Blast FungusMagnaporthe oryzae     

Abstract: In planta secretion of fungal pathogen proteins, including effectors destined for the plant cell cytoplasm, is critical for disease progression. However, little is known about the endoplasmic reticulum (ER) secretion mechanisms used by these pathogens. To determine if normal ER function is crucial for fungal pathogenicity, Magnaporthe oryzae genes encoding proteins homologous to yeast Lhs1p and Kar2p, members of the heat shock protein 70 family in Saccharomyces cerevisiae, were cloned and characterized. Like t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 78 publications
4
126
0
Order By: Relevance
“…The importance of effector accumulation in BICs to the compatible interaction is highlighted by the general absence of fluorescent effectors in BICs in the incompatible interaction (Mosquera et al, 2009;Yi et al, 2009). Although faint fluorescence from effector:FPs was sometimes observed in cells undergoing R gene-mediated HR, fully developed fluorescent BICs were not observed.…”
Section: A Novel Interfacial Structure Associated With Rice Blast Dismentioning
confidence: 97%
See 2 more Smart Citations
“…The importance of effector accumulation in BICs to the compatible interaction is highlighted by the general absence of fluorescent effectors in BICs in the incompatible interaction (Mosquera et al, 2009;Yi et al, 2009). Although faint fluorescence from effector:FPs was sometimes observed in cells undergoing R gene-mediated HR, fully developed fluorescent BICs were not observed.…”
Section: A Novel Interfacial Structure Associated With Rice Blast Dismentioning
confidence: 97%
“…However, we cannot rule out a role for differential effector expression because it remains possible that proteins that are highly expressed in BIC-associated cells are redistributed throughout the IH by cytoplasmic streaming through septal pores. At least initially, AVR-Pita1 appears to be secreted into BICs using the normal fungal ER-mediated secretion machinery because mutation in the ER chaperone LHS1 with a role in secretion severely impairs its BIC accumulation and its function in triggering Pita-mediated HR (Yi et al, 2009). Another study suggested that M. oryzae uses different secretion mechanisms in planta because the APT2 gene, which encodes a Golgi-localized P-type ATPase, appears to only be involved in secretion of the tested AVR effector and a subset of extracellular enzymes (Gilbert et al, 2006).…”
Section: A Novel Interfacial Structure Associated With Rice Blast Dismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the hygunPA(788-923)-HA protein in the pellet fraction (although less than observed in the self-incompatible colony) from the self-compatible colony may be due to our use of a trpC promoter to drive fusion protein expression. Previous studies have observed that expression from strong, constitutive promoters causes some overexpressed protein to become insoluble (Yi et al 2009;Tegel et al 2011), including studies that examine fungal protein complexes involved in nonself recognition (Mathur et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was isolated from the frozen fungal and plant tissues with Easy-spin TM total RNA extraction kit (iNtRON Biotechnology, Seoul, Korea) according to the manufacturer's instruction. To quantify levels of transcript, quantitative RT-PCR was performed as described [78]. Briefly, 5 mg of total RNA was reverse transcribed into first-strand cDNA with oligo (dT) primer using SuperScript TM First-Strand Synthesis System (Invitrogen TM Life Technologies, Carlsbad, CA, USA) according to the manufacturer's instruction.…”
Section: Nucleic Acid Manipulation and Polymerase Chain Reactionmentioning
confidence: 99%